OPTIMIZATION OF ABIOTIC FACTORS IN Schizophyllum commune TO DETERMINE ITS LIGNINOLYTIC ACTIVITIES AND ANTIBACTERIAL PROPERTIES - NUR DIYANA BINTI ROSNAN (2021)
Agricultural lignocellulosic waste is a potential source of serious environmental pollution. Studies on Schizophyllum commune Fr. as a lignocellulose degrader and its antibacterial properties, which are controlled by abiotic factors, can play an important role to better understand this species for the degradation of various lignocellulosic waste. In this study, the ligninolytic enzyme activities of S. commune and its antibacterial activities were investigated. The results showed that a higher level of mycelium formation of S. commune was observed in malt extract agar medium supplemented with yeast extract and glucose (MYGPA) at pH 5 and 28°C. The aeration factor significantly affected (p < 0.05) the growth, density of mycelium, and fruiting body formation of S. commune, based on oxygen and carbon dioxide consumption. Furthermore, eight substrates were investigated to compare their ability in producing higher activities among three ligninolytic enzymes under similar conditions. It was found that the maximum lignin peroxidase activity (1378.69 ± 41.76 U/ml) was obtained using coconut leaves as the subtrate , while manganese peroxidase showed its maximum activity (16.82 ± 4.36 U/ml) when using banana leaves, and laccase (49.00 ± 18.35 U/ml) when using spiny bucida after eight days in solid state fermentation (SSF). The complex structures of different lignocellulose materials were found to be degraded differently by S. commune as observed through the scanning electron microscope (SEM). Meanwhile, S. commune antibacterial activities against food poisoning bacteria, namely two types of Gram-positive bacteria (Bacillus cereus and Staphylococcus aureus) and three types of Gram-negative bacteria (Escherichia coli, Salmonella Typhimurium, and Pseudomonas aeruginosa) were investigated. The crude extract of S. commune was obtained from its cultivated fruiting body in rubber sawdust using different extraction solvents (100% methanol, 80% methanol, 80% acetone, 80% dichloromethane, and 80% ethyl acetate). S. commune 80% ethyl acetate extract was found to be the most effective in suppressing the growth of S. aureus. Furthermore, the minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) of this extract against S. aureus were 50 mg/ml and 100 mg/ml, respectively. The findings show that based on optimal environmental factors, S. commune has the ability to use agricultural waste lignocellulose as an alternative growth subtrate to rubber sawdust, which can benefit the proper waste management, while its antibacterial properties can be beneficial to the pharmaceutical industry.